MATHEMATICAL DESCRIPTION OF THE SPECIFIC HEAT CAPACITY OF THE WOOD ABOVE THE HYGROSCOPIC RANGE DURING WOOD FREEZING (Innovation in Woodworking Industry and Engineering design, 2026)
A mathematical description of the specific heat capacity c of wood above the hygroscopic range during wood freezing has been suggested. The description takes into account the physics of the freezing process of both the free and the hygroscopically bound water in the wood. It reflects also the influence of the fiber saturation point of wood species on the value of their c during wood freezing and the influence of the temperature on the fiber saturation point of the wood during its freezing. A software program has been prepared for the computation of c ac-cording to the suggested mathematical description. With the help of the program, computations have been done for the determination of c of often used in veneer and plywood production beech and poplar wood with moisture content 0.4 kg∙kg-1≤ u≤1.2 kg∙kg-1 at the temperature range between 0 oC and –60 oC during freezing of the wood.